LEGAL ASPECT OF PAYMENT OF THE AVERAGE AMOUNT OF CASH SUPPLY TO MILITARY SERVANTS ON THE BASIS OF A COURT DECISION - Kopach, R.; Ostapenko, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article analyzes the problematic issues regarding the payment of cash benefits to servicemen in case of violation of the term of obligatory social benefits upon dismissal. It is determined that during 2018–2020 there is a practice of applying the norms of labor legislation of Ukraine to recover from the military units of the Armed Forces of Ukraine the average amount of cash during the delay of full payment of a serviceman upon discharge from military service. It is noted that this state of affairs puts excessive financial pressure on the state defense budget, and therefore it is necessary to clarify the legitimacy of the application of labor legislation to servicemen in terms of payment of the average amount of cash for the delay in discharge from military service. It is substantiated that the norms of special legislation have an exclusive advantage over the norms of labor legislation in resolving disputes concerning the full calculation of servicemen upon discharge from military service. Emphasis is placed on the fact that the practice of the European Court of Human Rights regarding the payment of average earnings to individual citizens of Ukraine during the delay in payment upon dismissal is ambiguous. It was found that at the regulatory level there is no procedure for calculating the average amount of cash collateral. It is noted that the application of the analogy of the procedure for calculating the average salary of employees is technically impossible given that the structure of monetary support of servicemen and its economic essence is different from the structure and nature of wages. It is proposed as a direction of further research to develop a compromise mechanism in the system of special legislation to strengthen the responsibility of officials of military units of the Armed Forces of Ukraine for late and incomplete payment of servicemen upon discharge from military service.
Keywords: average monthly cash security, average earnings, settlement upon dismissal, legality of payment, compensation for delay in settlement upon dismissal, norms of labor and special legislation